Elucidation of mechanism for host response to VHSV infection at varying temperatures in vitro and in vivo through proteomic analysis. Issue 88 (May 2019) - Cho, Se-Young; Protzman, Rachael A.; Kim, Yeong O.; Vaidya, Bipin; Oh, Myung-Joo; Kwon, Joseph; Kim, Duwoon
Abstract: Seasonal temperature has a major influence on the infectivity of pathogens and the host immune system. Viral hemorrhagic septicemia virus (VHSV) is one such pathogen that only causes the mortality of fish at low temperatures. This study aims to discover the host defense mechanism and pathway for resistance to VHSV at higher temperatures. We first observed the VHSV infection patterns at low and higher temperatures in fathead minnow (FHM) cells (20 °C and 28 °C) and zebrafish (15 °C and 25 °C). In comparison to the 20 °C infection, FHM cells infected at 28 °C showed decreased apoptosis, increased cell viability, and reduced VHSV N gene expression. In zebrafish, infection at 25 °C caused no mortality and significantly reduced the N gene copy number in comparison to infection at 15 °C. To explore the antiviral infection mechanisms induced by high temperature in vitro and in vivo, the changes in the proteomic profile were measured through UPLC-MS E analysis. ACADL, PTPN6, TLR1, F7, A2M, and GLI2 were selected as high temperature-specific biomarkers in the FHM cell proteome; and MYH9, HPX, ANTXR1, APOA1, HBZ, and MYH7 were selected in zebrafish. Increased immune response, anticoagulation effects, and the formation of lymphocytes from hematopoietic stem cells were analyzed as functions that were commonly induced by high temperature in vitro and in vivo . Among these biomarkers, GLI2 was predicted as an upstream regulator. When treated with GANT58, a GLI-specific inhibitor, cell viability was further reduced due to GLI2 inhibition during VHSV infection at varying temperatures in FHM cells, and the mortality in zebrafish was induced earlier at the low temperature. Overall, this study discovered a new mechanism for VHSV infection in vitro and in vivo that is regulated by GLI2 protein. Graphical abstract: Image 1 Highlights: Temperature influences VHSV infection in FHM cells and zebrafish with antiviral effects at higher temperatures. Comparison of proteomic profiles of both organisms was applied. Commonly modulated functions in each proteome were hematological system development and inflammatory response. GLI2 was found to be a main regulator of host antiviral defense against VHSV infection.